Estudio de la producción, beneficiado y comercialización de cacao para los sectores de nueva esperanza San Alfonso independencia y Santa Martha - Bermeo Zúñiga, Jaime Lucio (2006)
The present work is part of the definitive Studies of the Subproject Intercantonal of benefited production and commercialization of cocoa in the low areas of Pucará, Ponce Enríquez and Pijilí", proposal that you development in Agreement with Camilo Ponce Enríquez M. I. Municipalidad, The University of Machala through the Department of Linking with the Community of the Ability of Agricultural Sciences and the Foundation Progresso and Desarrollo PRODE, the project is financed by the PROLOCAL through funds of Desarrollo IDB'S Interamerican Bank, the Municipality and the cacaoteros of the intervention area. . The surveys were carried out in the properties cacaoteras of San Alfonso's sectors, Santa Martha, Independence and New Esperanza belonging to the Canton Camilo Ponce Enríquez of the County of the Azuay, the outlined objectives were: OBJECTIVES: For the Component of: "I study of the productive offer and commercialization cacaotera: 1. integral diagnosis of the productive and commercial offer. 2. proposal of improvement continues of the productive system, and of the commercialization system. For the Component of: "Partner - Organizational - Self-management": 1. integral diagnosis of the structure organizational beneficiary. 2. to outline a structure partner - organizational for viabilizar the installation of the project, with the support of a system of active, equal participation and empowered with all and each one of the potential partners of the sub-project. The sectors studied in the productive chain have like general average among National cocoa and CCN-51 6.19qq/ha/año that it is low in relation to the average of the Country that is in 8.2qq/ha/año and more even to the average of the sector of Orange grove than it is very close and it is of 10qq/ha/año, but that with the training it is planned to end up producing 9qq/ha/año, when the project that will last two years concluding. The project has the back and the enthusiasm of all its producing partners for what won't be difficult to achieve the goal traced since it will be given training, technical attendance and permanent accompaniment and the incentive of the price that it will improve it will be the guarantee of the results. Concerning the Partner-organizational component 27% of weaknesses exists that the same as to the component of the productive chain it will be qualified to the producers to improve in a two year-old lapse its organizations and all the variables that it contains the component. In a same way one will work in the artificial life of an organization that locks to the four organizations of first degree in one of second degree and power to market in associative form to a better price and from a single storing center that will be located in San Alfonso's sector.